Cross-transmission of vancomycin-resistant Enterococcus in patients undergoing dialysis and kidney transplant - Fram,D. (2010)
The objective of this study was to investigate the occurrence of vancomycin-resistant Enterococcus (VRE) cross-transmission between two patient groups (long-term dialysis and kidney transplant patients). Molecular typing, by automated ribotyping with the RiboPrinter Microbial Characterization System (Qualicon, USA), was used to analyze VRE isolates from 31 fecal samples of 320 dialysis patients and 38 fecal samples of 280 kidney transplant patients. Clonal spread of E. faecalis and E. casseliflavus was observed intragroup, but not between the two groups of patients. In turn, transmission of E. gallinarum and E. faecium between the groups was suggested by the finding of vancomycin-resistant isolates belonging to the same ribogroup in both dialysis and transplant patients. The fact that these patients were colonized by VRE from the same ribogroup in the same health care facility provides evidence for cross-transmission and supports the adoption of stringent infection control measures to prevent dissemination of these bacteria.